Model test study on rapid reinforcement technology for shallow soft foundations in sichuan basin - Huang, Rui; Wang, Bo; Zhang, Le; Xiao, Dong; Li, Bing; Zhang, Junyun (Frontiers in Earth Science, 2025)
Rapid reinforcement methods for shallow soft foundations are critical for guiding practical applications in subgrade engineering. This study uses model tests to examine how the particle size and number of compacted rock fill layers affect the reinforcement performance of shallow soft foundations. It analyzes the load-settlement behavior, key mechanical factors, and the long-term stability of the reinforced foundation. The results show that: (1) Foundation settlement decreases as the number of compacted layers increases, while both the ultimate bearing capacity and deformation modulus increase significantly. With layer counts rising from 0 to 1, 2, and 3, the bearing capacity improved by 113.27%, 47.91%, and 69.21% on average, while the deformation modulus increased by 39.54%, 12.16%, and 63.95% on average, depending on the rock fill size. Notably, using 9 cm rock fill and 3 compaction layers yielded a remarkable 709.83% increase in ultimate bearing capacity and a 329.17% increase in deformation modulus compared to the untreated foundation. (2) Both the ultimate bearing capacity and deformation modulus increase with higher maximum compacted stress. Empirical formulas were developed to predict bearing capacity and deformation mod-ulus, accounting for maximum compacted stress and particle size. Validation with experimental data showed that the formulas had an average relative error of less than 7.37%. (3) After an initial significant settlement increase (ranging from 76.03% to 208.29% at different points) due to the first rainfall saturation, the reinforced foundation remained stable, with minimal further impact (only 0.04%–2.15% additional settlement) from continued infiltration.